(untitled) (Scientific journal of the Fergana State University, 2026)
This study provides information on the herbarium specimens of the family Polygonaceae Juss. collected from the Fergana Valley and preserved in the TASH database of the National Herbarium of Uzbekistan, as well as in major international herbarium collections. The family Polygonaceae remains one of the insufficiently investigated taxa in the region. Based on the analysis, we compiled a list of nearly 400 specimens collected since 1913, representing 9 genera and 46 species. However, the currently available data are not sufficient to fully elucidate the species composition and distribution patterns of the flora. Therefore, subsequent research stages will involve targeted field surveys and a complete species inventory to develop a georeferenced database.